Titration of Antibodies and Application of the KAP Strategy for Hepatitis B in Students and Teachers - Sreeharsha, Nagaraja; Epstein, Itzjak Kadar; Asdaq, Syed Mohammed Basheeruddin; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alhomrani, Majid (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Hepatitis B can be prevented through a complete vaccination scheme. In clinical practice, dentistry personnel is 6 times more likely to get this disease than people who perform other activities. To determine the level of protection and establish the degree of knowledge, attitudes, and practices (KAP) against Hepatitis B in the students and clinical lecturers in a dental clinic. Methods: Descriptive cross-sectional study. For the KAP strategy, a structured survey was applied with 15 questions, and for the titration: antibody level, concentration according to five categories ranging from negative or very poor to highly positive. The analysis of blood samples is carried out using ELISA in an immunology and molecular biology laboratory. Results: 71% of people present concentrations equal to or greater than 20 mIU/ml. In the KAP strategy, the highest rating was in the practical compo-nent with 50.8%, followed by knowledge with 40%, an acceptable score, and attitudes 27.7% with an insufficient score. Within this survey, 38% of the participants know the routes of transmission for Hepatitis B, 51% present the complete vaccination scheme, and 75.4% report not having been involved in an accident with biological risk. Conclusion: KAP strategy, knowledge about Hepatitis B; was represented in the acceptable rating, insufficient attitudes, and outstanding practices
Keywords: Hepatitis B; Antigen; Antibody; ELISA; Hemodialysis